Teacher Career Orientation: Indonesian Perspective - Khaeriah, Khaeriah; Hidayat, Dede Rahmat; Herdi, Herdi (Universitas Muhammadiyah Metro, 2021)
The teacher's role is significant in determining the quality of education, so the quality of teachers also needs to be considered. The government has made various efforts to improve the quality of teachers. One of the factors for the low quality of teachers is the teacher's perspective on his profession, which is still not quite right. The profession is closely related to career development. Every individual must have hope to be successful in achieving their career. Efforts to achieve a career position will be related to the development of career orientation. Career orientation to teachers is an interesting thing to discuss because teachers are often considered as someone who has an ideal personality as a role model. This study aims to describe the career orientation of teachers based on educational background, gender, and regional origin. The research method uses a literature study. Based on the results of this study, who found that in developing career orientation, teachers must pay attention to career self-concept, which is divided into 8 career anchors, namely technical competence, managerial competence, autonomy, job security/geographical security, creativity, and entrepreneurship, pure challenge, lifestyle integrity. Educational background and linearity will affect the skills and professionalism of teachers. Gender affects teacher career orientation, and we can see that the number of female teachers in Indonesia is more than male. The origin of the area affects the career orientation of teachers because it is related to equal distribution of education, development, the development of science and technology.